FAKTOR YANG MEMPENGARUHI KINERJA PERAWAT DALAM PENERAPAN PROSES KEPERAWATAN DI RSUD TOTO KABUPATEN BONE BOLANGO - Buheli, Kartin (Jurnal Sainstek, 2012)
This research aim to analyse factor influencing nurse performance in applying of treatment process [in] RSUD Toto Sub-Province of Bone Bolango. this Type Research is analytic research [of] observasional with method